Employment Guarantee Scheme In Maharashtra - A Preliminary Observation Design Instruments Instructions etc. - Planning Commission (Planning Commission, 1993)
The Government of Maharashtra vide its letter dated June 25, 1992 has proposed a joint evaluation of the Scheme to be taken up by Programme Evaluation Organisation of the Planning Commission in collaboration with the Government of Maharashtra. OBJECTIVES 20 Keeping in view the lasuea referred to by the State Government and discussion in the internal meeting with Adviser(LEM)it is proposed to restrict the objectives as follower (1) To understand organisation and administration of Scheme including changes in the contents, its working and arrangements for monitoring.
Programme Evaluation Organisation Planning Commission (Government of India)